Relationships between caused by drinking of bioactive water Naftussya changes in urine lithogenicity and neuro-humoral-immune factors in humans with theirs abnormalities - Flyunt, Victor R.; Flyunt, Igor-Severyn S.; Fil’, Vitaliǐ M.; Kovbasnyuk, Marta M.; Hryvnak, Rostyslav F.; Popel, Svitlana L.; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Objective. Spa Truskavets’ (Ukraine) considered to be indicated for the treatment and metaphylaxis renal stone disease. However, data on the effect of balneotherapy on the parameters of urine Lithogenicity ambiguous. This is due, perhaps, ambiguous influence balneotherapy on the neuroendocrine factors regulating exchange of electrolytes and uric acid. Aim: to find out the influence drinking of bioactive water Naftussya on urine lithogenicity and neuro-humoral-immune factors in humans with theirs abnormalities. Methods. The object of observation were ten women and ten men aged 33-76 years without clinical diagnose but with dysfunction of neuro-endocrine-immune complex and metabolism. In daily urine and blood we determined the content of electrolytes and nitrogenous metabolites, estimated parameters of immunity, recorded conductivity of acupuncture points and heart rate variability (HRV). After examination volunteers within 7 days used bioactive water Naftussya (250 ml three times a day), then repeated the tests listed. Results. Lithogenicity urine Index (Lith) calculated by formula: Lith=(Uric acid•Calcium/Magnesium•Creatinine)0,25. In 3 people initial normal Lith (0,65÷0,81 units) increased by 0,08÷0,16 units. In 4 people with normal or high Lith its changes were not detected (-0,01÷+0,01). In 12 people from a wide range of primary Lith (0,62÷1,07) it lowered by 0,03÷0,12 un. Even in a man maximum level of Lith (1,45 un.) down to the upper limit of normal (0,84 un.). Found a strong correlation between changes in Lith and a number parameters of HRV, metabolism and immunity. Conclusion. The use of bioactive water Naftussya causes ambiguous changes in Lithogenicity of urine, related to ambiguous changes in HRV, metabolism and immunity.